Meta Analisis Efektivitas Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa SD - Afan Chrislando (Peneliti.net, 2020)
The purpose of this study was to determine the meta-analysis of the effectiveness of the problem-based learning model to be effective on the critical thinking skills of elementary school students. Problem Based Learning learning model is a learning model based on problem solving which can increase the critical thinking skills of elementary school students. This study uses the Meta Analysis method, the researcher first formulates the research problem, then continues by presenting the data with existing research to be re-analyzed using 20 research articles. Based on the results of the analysis, it turns out that the Problem Based Learning learning model can increase the critical thinking skills of elementary school students with a result of 1.10 which is categorized as large.